Implementation of Multicultural Education through PPKn Learning in Building Tolerance Attitudes of Elementary School Students: A Case Study at SDN 011 Lakahang - H., Hasnawia; Purwantiningsih, Ary; Puryanto, Sidik (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This research explores the application of multicultural education principles within Pancasila and Citizenship Education (PPKn) curriculum to cultivate tolerance attitudes among fourth-grade students at SDN 011 Lakahang, located in Mamasa Regency, West Sulawesi Province. Employing qualitative descriptive methodology, this investigation examines pedagogical strategies for integrating multicultural values within a predominantly homogeneous educational environment. Data collection utilized in-depth interviews, systematic observations, and comprehensive documentation analysis involving educators, students, families, and community stakeholders. Research outcomes demonstrate that strategic implementation of multicultural education through PPKn instruction effectively promotes tolerance development through diverse pedagogical approaches including content diversification, knowledge construction facilitation, prejudice mitigation, and equitable teaching practices. The investigation identifies implementation challenges including restricted diversity exposure and provides valuable insights regarding factors that influence successful multicultural education delivery in homogeneous educational contexts.